High-risk features of basilar artery atherosclerotic plaque - Li, Shaojun; Wei, Jiana; Huang, Ruiyun; Li, Chenghao; Chen, Hongbing; Qiu, Zhihua; Jiang, Yongjun; Wu, Li (Frontiers in Neurology, 2022)
Introduction High-resolution MRI is used to characterize the atherosclerotic plaque. The present study aimed to determine the high-risk features of the basilar artery atherosclerotic plaque. Methods Patients with advanced basilar artery stenosis were screened. The features including ruptured fibrous cap (RFC), lipid core, intraplaque hemorrhage, plaque enhancement and calcification were assessed by high-resolution MRI. The relationship of the features with acute infarction was analyzed. Results From June 1, 2014, to December 31, 2018, a total of 143 patients with 76 new strokes were included. RFC was identified in 25% of symptomatic and 10.4% of asymptomatic patients. Intraplaque hemorrhage was identified in 48.7% of symptomatic and 25.4% of asymptomatic patients. RFC (3.157, 95% CI 1.062 to 9.382, P=0.039) and intraplaque hemorrhage (2.78, 95% CI 1.127 to 6.505, P=0.026) were independent risks for acute infarction. Conclusions Our study showed that RFC and intraplaque hemorrhage of basilar artery plaque were independent risks for acute infarction.